(untitled) (Global Journal of Human-Social Science, 2014)
Until the first decades of the twentieth century, hagiography was seen with mistrust by historians. Its pious aims and fabulous content made us resistant to include them on the list of reliable documents. The methodological innovations that followed thereafter increased the confidence of historians in it and hagiography has become more and more integrated to the testimonies employed by historical analyses. However a problem about the status of the documentation persisted: the doubt concerning the recognition of the performance of authorial intention in the composition of unsigned narratives that originated themselves from relatively unknown writers or whose content seemed to repeat, without any originality, an earlier tradition. This problem was particularly significant in the treatment historians gave to the most widespread medieval hagiographical work, The Golden Legend. Written in the last third of the 13 th century and based on ancient hagiographical material compiled by the Dominican Jacobus de Voragine, the work was an immediate and booming success -with about a thousand Latin manuscripts coming from various regions of Western Christendom. Here we intend to discuss the existence of authorial intention in its composition in a twofold manner.